Reassessing the pathogenicity of c.2858G>T(p.(G953V)) in COL4A5 Gene: report of 19 Chinese families - Zhang, Yanqin (Eur J Hum Genet, 2019)
X-linked Alport syndrome (XLAS) is an inherited renal disease caused by mutations in COL4A5 gene. The c.2858G>T(p.(G953V)) in COL4A5 gene (rs78972735) has been considered pathogenic previously. However, there are conflicting interpretations of its pathogenicity recently. Here we presented 19 Chinese families, out of which 36 individuals (18 probands and 18 family members) carried the c.2858G>T(p.(G953V)) in COL4A5 gene. The clinical manifestations and genetic findings of them were analyzed. We found there were no clinical features of Alport syndrome not only in six probands with c.2858G>T(p.(G953V)) in COL4A5 plus pathogenic variants in other genes (e.g., WT1, ADCK4, NPHP1, TRPC6, COL4A4, and PAX2) but also in another six probands with only the c.2858G>T(p.(G953V)) variant. The other six probands with a combination of c.2858G>T(p.(G953V)) and another pathogenic variant in COL4A5 had XLAS. Eleven family members (11/18, nine females and two males) who had only the c.2858G>T(p.(G953V)) variant were asymptomatic. These two males (at age of 42 and 35 years) had normal result of urine analysis and no more clinical traits of Alport syndrome. We conclude c.2858G>T(p.(G953V)) in COL4A5 gene is not a pathogenic variant for XLAS. Individuals should not be diagnosed as XLAS only based on the detection of c.2858G>T(p.(G953V)) in COL4A5 gene.